Recent Advances in the Synthesis of Thienoquinolines (Quinoline‐fused heterocycle). Issue 12 (13th October 2020) - Teja, Chitrala; Nawaz Khan, Fazlur‐Rahman
Abstract: Over the past few decades, thienoquinolines have gained considerable attention due to their biological and synthetic applications. Few reports have been disclosed on Thienoquinoline synthesis. Hence, in the present review, we provided a comprehensive update on the synthesis of Thienoquinolines. A brief description of the preparation procedure, reactivity, and mechanisms are included, where as possible. Respectively, the thienoquinoline synthesis is classified and summarized based on its reactivity, so it will help the researchers to obtain knowledge over the previous literature reports to overcome their problems in designing a new process. Abstract : Thienoquinoline a fused quinoline heterocycle with a sulfur atom, known to have several bioactivities in medicinal chemistry. Its synthetic utility over organic transformations to produce varied molecules with biological importance. In this review, we discussed about the synthesis of Thienoquinolines from the beginning, and a brief description of the preparation procedure and reactivity are enclosed.